1992
DOI: 10.1103/physreva.45.1018
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation kinetics and aggregate morphology in the intermediate regimes between diffusion-limited and reaction-limited cluster aggregation

Abstract: We investigate the kinetics and fractal morphology of aggregating polystyrene latex in an intermediate region between diffusion-limited cluster aggregation (DLCA) and reaction-limited cluster aggregation (RLCA). The measurements are made by means of a low-angle elastic-light-scattering setup covering two decades in scattering wave vectors. For each aggregation run, the salt concentration c is changed and the samples are prepared under isopycnic conditions, to avoid differential sedimentation. The average clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
71
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 24 publications
9
71
0
1
Order By: Relevance
“…Numerous previous studies have shown an inverse relation between dr and coagulation rate (Lin et al 1989;Hackley and Anderson 1989;Areal et al 1990;Asnaghi et al 1992;Zhang and Buffle 1996) and this pattern is observed in the present study for aggregates formed by counterion screening in the presence of KC1 (Figure 8a). However, the coagulation rate for phosphate-induced destabilization (Figure 8b) shows a completely different trend.…”
Section: Discussionsupporting
confidence: 71%
“…Numerous previous studies have shown an inverse relation between dr and coagulation rate (Lin et al 1989;Hackley and Anderson 1989;Areal et al 1990;Asnaghi et al 1992;Zhang and Buffle 1996) and this pattern is observed in the present study for aggregates formed by counterion screening in the presence of KC1 (Figure 8a). However, the coagulation rate for phosphate-induced destabilization (Figure 8b) shows a completely different trend.…”
Section: Discussionsupporting
confidence: 71%
“…We initiate aggregation by adding MgCl 2 to a concentration of 6 mM; with initial volume fractions 4.6 3 10 23 # w # 1.58 3 10 22 , gels form within several hours, leading to macroscopically homogeneous structures. Static light scattering [4,10,12] from these gels at lower w confirms d f ϳ 1.9, slightly above the value expected for DLCA, and consistent with the initial aggregation being in the intermediate regime between 1064 0031-9007͞99͞82 (5)͞1064 (4) diffusion-and reaction-limited cluster aggregation; we note, however, that diffusion still dominates at longer times, leading to a well-defined average cluster size.…”
supporting
confidence: 81%
“…A new nonuniversal scaling relationship was proposed that collapses the size distribution at the small end of the size spectrum. Apart from the effect of initial conditions on the small end of the size spectrum, the van Dongen and Ernst predictions are consistent with reported experimental observations (12,13,15,(22)(23)(24)(25), Monte Carlo simulations of the coagulation process (26)(27)(28)(29), and analytical studies of the von Smoluchowski equation (30)(31)(32)(33). The λ and µ values for several physical coagulation kernels are listed in Table 1.…”
Section: Predictions For a Generalized Kernelsupporting
confidence: 83%